Effects of L1 Writing Experiences on L2 Writing Perceptions: Evidence From an English as a Foreign Language Context. Issue 6 (2nd November 2019) - Saeli, Hooman; Cheng, An
Abstract: The current study explored Iranian learners' prior L1 (i.e., Farsi) experiences, their L2 (i.e., English as a foreign language) writing-related perceptions, and the effects of these writing-related L1 experiences on L2 writing-related perceptions. The data were gleaned from 15 students in a wide range of proficiencies using qualitative interviews. Analysis of data subsequently revealed that the participants negatively evaluated their L1 writing experiences, that the learners attached low importance to the skill of writing in English, and that the learners drew on their L1 experiences in forming their L2 writing perceptions. In particular, the participants believed that their L1 writing experiences were not "useful, " a perception often transferred to L2 writing contexts as well. The findings of the study highlight the importance of incorporating awareness-raising strategies (e.g., needs analysis) which can help students to grow more informed about the status of L1 and L2 writing in various contexts (e.g., academic and professional).